KNOWJI Y SUS BENEFICIOS EN El APRENDIZAJE DE LOS ESTUDIANTES DE BACHILLERATO TECNICO DE LA UNIDAD EDUCATIVA FRANCISCO JAVIER AGUIRRE ABAD PERIODO ACADÉMICO ABRIL - AGOSTO 2024 - RIVAS CARRANZA ROBERTO FELIPE (2024)
The purpose of the following research work is to determine the ease of Knowji as a learning tool in the educational process of students, for learning the English language and obtaining information, it is an essential tool for the execution of notes in the investigative context. It is essential for this reason that Knowji and its benefits are presented in the learning of technical high school students of the Francisco Javier Aguirre Abad educational unit academic period April - August 2024 The main objective of this descriptive and quantitative study was to analyze the contribution of Knowji in the learning of the English language of the students of the Francisco Javier Aguirre Abad educational unit with the participation of 70 high school students surveyed technician. The results show that there is a contribution of Knowji in the learning process of technical high school students and an adequate implementation in the classroom. This suggests that students have greater exposure to these tools and methodologies in the classroom, which It can be beneficial to your learning process. The study determined that the use of the Knowji technological tool can be beneficial and have a positive effect on the learning of the English language by technical high school students, allowing students to understand the subject and academic activities, thus optimizing their learning process. significant.